Further delineation of the phenotype of truncating KMT2A mutations: The extended Wiedemann–Steiner syndrome. Issue 2 (19th October 2016) - Sun, Yu; Hu, Guorui; Liu, Huili; Zhang, Xia; Huang, Zhuo; Yan, Hui; Wang, Lili; Fan, Yanjie; Gu, Xuefan; Yu, Yongguo
Abstract : KMT2A mutations cause Wiedemann–Steiner syndrome (WDSTS), which is characterized by hypertrichosis cubiti, short stature, and distinct facial features in general. Here, we report two Chinese boys with novel nonsense KMT2A mutations. Most of their phenotypes are concordant with WDSTS. They, however, lack the key WDSTS feature—hypertrichosis cubiti. Additionally, their transverse palmar creases are absent. We further summarized the genotypes and phenotypes of the KMT2A mutation carriers. The consensus phenotypes include postnatal growth retardation, developmental delay, short stature, and intellectual disability. The common facial features include thick eyebrows, long eyelashes, downslanting, and narrow palpebral fissures, wide nasal bridge, and broad nasal tip. They have generalized hypertrichosis. A hairy back can be observed as frequently as hairy elbows in patients with KMT2A mutations. Absent palmar proximal transverse creases are only observed in these two Chinese boys. This might be due to the difference in ethnic background. Thus far, all mutations in KMT2A are located before the FYRC domain. They would truncate KMT2A mRNA transcripts. Haploinsufficiency of the histone methyltransferase activity would therefore influence transcriptional regulation. © 2016 Wiley Periodicals, Inc.